11 - ( 15 + 11 ) = x - ( 25 - 9 )
11 - 26 = x - 16
- 15 = x - 16
- 15 + 16 = x
1 = x.
Nhớ tick mình nhé !
11 - ( 15 + 11 ) = x - ( 25 - 9 )
11 - 26 = x - 16
- 15 = x - 16
- 15 + 16 = x
1 = x.
Nhớ tick mình nhé !
Tìm số nguyên x, biết: 11 – (15 + 11) = x – (25 – 9)
Tìm số nguyên x ,biết:
11-(15+11)=x-(25-9)
Tìm số nguyên x , biết:
11-(15+11)=x-(25-9)
Bài 1 : Tìm số nguyên x biết :
a, 11 - ( 15 + 11 ) = x - ( 25 - 9 )
b, 2 - x = 17 - ( - 5 )
c, x - 12 = ( - 9 ) - 15
d, 9 - 25 = ( 7 - x ) - ( 25 + 7 )
Tìm số nguyên x,biết:
11-(15+11)=x-(25-9)
Tìm số nguyên x, biết :
a) 11 - (15 + 21) = x -(25 - 9)
b) 9 - 25 = (7 - x) - (25 + 7)
Tìm số nguyên x
a) 2 - x = 17 - (-5)
b) x - 12 = -9 - 15
c) 11 - ( 15 + 11) = x - ( 25 - 9 )
d) x - 25 = ( 7 - x ) - ( 25 + 7 )
tick liền 5 ngày, help me, trình bày chi tiết nha
tìm số nguyên x, biết:
a) 11- (15 + 11) = x - (25 - 9)
b) 2 - x = 17 - (-5)
c) x - 12 = (-9) -15
2k5 cùg tủi pr ik #u
tìm số nguyên x, biết
( 2x + 4 ) ( x + 2 ) = 0
x - ( 25 - 9 ) = 11 - ( 15 + x )